Clinical outcomes of drug-eluting stents versus bare-metal stents in patients with cardiogenic shock complicating acute myocardial infarction. (15th July 2016) - Chen, Dong-Yi; Mao, Chun-Tai; Tsai, Ming-Lung; Chen, Shao-Wei; Lin, Yu-Sheng; Hsieh, I-Chang; Hung, Ming-Jui; Wang, Chao-Hung; Wen, Ming-Shien; Cherng, Wen-Jin; Chen, Tien-Hsing
Abstract: Background: To investigate the cardiovascular (CV) outcomes of drug-eluting stents (DESs) versus bare-metal stents (BMSs) in patients with acute myocardial infarction (AMI) complicated by cardiogenic shock (CS). Methods: Data from the Taiwan National Health Insurance Research Database was analyzed between January 1, 2007 and December 31, 2011. A total of 3051 AMI patients in CS were selected as the study cohort. Their clinical outcomes were evaluated by comparing 1017 subjects who used DESs to 2034 matched subjects who used BMSs. Results: The risk of the primary composite outcome (i.e., death, myocardial infarction, stroke, and coronary revascularization) was significantly lower in the DES group compared with the BMS group [56.1% vs. 66.2%, hazard ratio (HR), 0.74; 95% CI, 0.67–0.81] with a mean follow-up of 1.35 years. The patients who received DESs had a lower risk of coronary revascularization (HR, 0.78; 95% CI, 0.67–0.91) and death (HR, 0.70; 95% CI, 0.62–0.79) than those who used BMSs. However, the risks of myocardial infarction (HR, 0.89; 95% CI, 0.66–1.18), ischemic stroke (HR, 1.02; 95% CI, 0.67–1.53) and major bleeding (HR, 0.80; 95% CI, 0.56–1.14) were similar between the two groups. Conclusions: Among patients with CS complicating AMI, DES implantation significantly reduced the risk of percutaneous coronary revascularization and death compared to BMS implantation.